OPEN INNOVATION AS A STRATEGIC MODEL OF MODERN BUSINESS - Nataliia Revutska (European Scientific Journal, ESJ, 2014)
The paper considers the characteristics of two models of innovation management in business: a “closed” and “open” innovation models. The traditional model of closed innovation suggests that it is created, used and developed within one company. The company concentrates all innovation processes within business, oversees its implementation and uses the results of own research and development. Formation and development of a knowledgebased economy requires shifting to a model of “open” innovation. This is due to the need of involvement in the process of new knowledge creating a wide range of professionals, academics and research centers from different countries and areas. Therefore, the possibility to organize a full cycle of innovation within a company is becoming increasingly difficult in an environment where innovation life cycle is reduced. Companies with “open” innovation transfer innovative processes to professional research laboratories, research centers and independent scholars. Inside the company stays a development department whose main task is the selection of the most promising start-ups, research proposals and their rapid commercialization. The concentration of innovation efforts of different participants of innovation chain development, the creation of conditions for the rapid completion of all stages of the invention into production will ensure successful development of “open” innovation model in the long term.